iPad-assisted percutaneous nephrolithotomy (PCNL): a matched pair analysis compared to standard PCNL - Rassweiler-Seyfried, Marie-Claire; Rassweiler, Jens; Weiß, Christel; Meinzer, Hans-Peter; Maier-Hein, Lena (World journal of urology, 2020)
To compare iPad-assisted (Apple Inc., Cupertino, USA) percutaneous access to the kidney to the standard puncturing technique for percutaneous nephrolithotomy (PCNL). For the iPad-assisted PCNL, a computed tomography is performed prior to surgery, using fiducial radiopaque markers. The important anatomical structures (i.e. kidney, stones) are segmented using specific software enabling the superimposition of images semi-transparently on the iPad by marker-based navigation. Twenty-two patients underwent an iPad-assisted percutaneous puncture of the kidney for PCNL. Twenty-two patients of the clinical database from the Urological Department SLK Hospital Heilbronn, who underwent the standard puncturing technique, were matched to these patients. Matching criteria were age, gender, stone volume, body mass index, stone site and the absence of anatomical variation. Puncture time, radiation exposure and number of attempts for a successful puncture were evaluated. All procedures were performed by two experienced urologists. The standard puncturing method consisted of a combination of ultrasound and fluoroscopy guidance. Chi-square and t test were used to ensure that there was no difference in the matching criteria between the groups. To compare the two methods, U test, Kruskal-Wallis and Chi-square test were used. Examination of radiation exposure showed a significant difference between the two groups in favour of the standard puncturing method (p < 0.01) and puncture time (p = 0.01). However, there was no significant difference in puncturing attempts (p = 0.45). The iPad-assisted navigation, with the objective being to puncture the renal collecting system, represents a new technique (IDEAL criteria 2b), which proved to be applicable in clinical practice, but still has potential for technical improvement.
Published online: 9 May 2019
Gesehen am 02.03.2020